Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from China - Bayarsaikhan, Ulziijargal; Li, Houhun; Im, Kyung-Hoan; Bae, Yang-Seop (Zootaxa, 2020)
Four new species, Diduga luteogibbosa n. sp., D. allodubatolovi n. sp., D. scalprata n. sp. and D. hainanensis n. sp. are described from China along with three newly recorded species, D. albicosta Hampson, 1891, D. nigridentata Bayarsaikhan & Bae, 2019 and D. hanoiensis Bayarsaikhan & Bae, 2019. A key to the Chinese species of the genus Diduga, with illustrations of adults and genitalia of examined species are presented.